(untitled) (Eureka Journal of Civil, Architecture and Urban Studies, 2026)
Façades (the outer "skins" of buildings) have transformed from passive static envelopes into intelligent, adaptive systems that regulate indoor–outdoor environments. With the growing use of façades in built space, façades are no longer the defining element of a building in terms of looks but also play an integral role in thermal performance of buildings as well as comfort of the occupants inside1. Architectural changes in durable materials and gadgets have led architects to move beyond conventional brute walls and immovable fenestration to versatile designs. In contrast, for instance, ventilated double-skin façades, moveable shading elements and smart glazing systems allow façades to adapt to the environmental conditions rather than resist 1. These high-performance façades are capable of modulating solar gain and natural ventilation to lower heating and cooling loads. Deploying such adaptive façades has been shown to reduce building energy use by up to 50% and results in considerably better thermal comfort over static façades [3]. In principle, modern façades combine insulation, daylight control and even energy generation (for example, photovoltaic glazing) to enable buildings to come as close to Net-Zero Energy targets as possible [4,3].